β-Fructofuranosidase and β –D-Fructosyltransferase from New Aspergillus carbonarius PC-4 Strain Isolated from Canned Peach Syrup: Effect of Carbon and Nitrogen Sources on Enzyme Production - Gustavo Carvalho do Nascimento; Ryhára Dias Batista; Claudia Cristina Auler do Amaral Santos; Ezequiel Marcelino da Silva; Fabrício Coutinho de Paula; Danylo Bezerra Mendes; Deyla Paula de Oliveira; Alex Fernando de Almeida (The Scientific World Journal)
β-fructofuranosidase (invertase) and β-D-fructosyltransferase (FTase) are enzymes used in industrial processes to hydrolyze sucrose aiming to produce inverted sugar syrup or fructooligosaccharides. In this work, a black Aspergillus sp. PC-4 was selected among six filamentous fungi isolated from canned peach syrup which were initially screened for invertase production. Cultivations with pure carbon sources showed that invertase and FTase were produced from glucose and sucrose, but high levels were also obtained from raffinose and inulin. Pineapple crown was the best complex carbon source for invertase (6.71 U/mL after 3 days of cultivation) and FTase production (14.60 U/mL after 5 days of cultivation). Yeast extract and ammonium chloride nitrogen sources provided higher production of invertase (6.80 U/mL and 6.30 U/mL, respectively), whereas ammonium nitrate and soybean protein were the best nitrogen sources for FTase production (24.00 U/mL and 24.90 U/mL, respectively). Fermentation parameters for invertase using yeast extract were YP/S = 536.85 U/g and PP = 1.49 U/g/h. FTase production showed values of YP/S = 2,627.93 U/g and PP = 4.4 U/h using soybean protein. The screening for best culture conditions showed an increase of invertase production values by 5.10-fold after 96 h cultivation compared to initial experiments (fungi bioprospection), while FTase production increased by 14.60-fold (44.40 U/mL) after 168 h cultivation. A. carbonarius PC-4 is a new promising strain for invertase and FTase production from low cost carbon sources, whose synthesized enzymes are suitable for the production of inverted sugar, fructose syrups, and fructooligosaccharides.